Self-selecting the number of repetitions in potentiation protocols: Enhancement effects on jumping performance - Dello Iacono, A.; Beato, M.; Halperin, I. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate whether providing athletes with a choice regarding the number of repetitions to complete in a potentiation protocol would enhance jumping performance compared with protocols in which the number of repetitions is predetermined. Methods: Fifteen male basketball players completed 4 testing sessions separated by 72 hours. In the first session, individual optimum power loads in the barbell jump squat were determined. In the following 3 sessions, the athletes completed 3 sets of 3 potentiation protocols using optimum power load jump squats in a partly randomized order: (1) The traditional condition included 6 repetitions per set, (2) the self-selected condition included a choice regarding the number of repetitions to complete per set, and (3) the imposed condition included the same number of repetitions per set as the self-selected condition, but the number was imposed on the athletes beforehand. The jumping performance was determined as jump squat test height and measured using a force platform before and 30 seconds, 4 minutes, and 8 minutes after completing the protocols. Results: The self-selected condition led to superior jumping performance compared with the 2 other conditions across all post measures (P < .05; range: 0.3-1.3 cm). Compared with the traditional condition, the imposed condition led to superior jumping performance across all post measures (range: 0.2-0.45 cm), although not statistically significant at post 4 minutes and post 8 minutes. Conclusions: Choice provision concerning how many repetitions to complete in a potentiation protocol is a useful performance-enhancing strategy. Improved potentiation-fatigue ratio and motivational factors are sought to explain these effects.